MODEL KOMUNIKASI DALAM PERSPEKTIF PENYELENGGARAN PELAYANAN AKTE KELAHIRAN DI KABUPATEN BOGOR - Subagja, Oetje (Universitas Djuanda, 2020)
In the implementation of public service birth certificates by the Department of Population and Civil Registry of Bogor Regency, it was identified that they were not optimal in fulfilling the demands and expectations of the community. Communication variables are exogenous latent variables that affect endogenous latent variables. Communication as a process of delivering and receiving information through certain media between service providers and service providers is correlated with service performance. Therefore, functional communication affects the quality of birth certificate services. The aim of this study is to analyze the public service communication model in the case of birth certificates. The method used is descriptive analysis. The population of this research is the people who have taken care of birth certificates and those who are processing birth certificates. These communities are located in RW areas in 47 villages/wards in Ciomas District, Ciawi District, Parung District, and Citerureup District. The research sample of 386 respondents was taken from a population of 1,115 people using a simple random sampling technique. Data analysis using Structural Equation Models Analysis and Frequency Distribution Analysis. The results showed that the magnitude of the influence of communication on the quality of birth certificate services was determined by personal skills and attitudes, interpersonal skills, and oral and written communication reaching 0.430, which is somewhat less strong but significant. The existence of such an influence proves that the quality of birth certificate services has a meaningful causal relationship. Keywords: communication, service, certificate